2020
DOI: 10.3390/ijms21072436
|View full text |Cite
|
Sign up to set email alerts
|

Human Melanoma-Cell Metabolic Profiling: Identification of Novel Biomarkers Indicating Metastasis

Abstract: Melanoma is the most aggressive type of skin cancer, leading to metabolic rewiring and enhancement of metastatic transformation. Efforts to improve its early and accurate diagnosis are largely based on preclinical models and especially cell lines. Hence, we herein present a combinational Nuclear Magnetic Resonance (NMR)- and Ultra High Performance Liquid Chromatography-High-Resolution Tandem Mass Spectrometry (UHPLC-HRMS/MS)-mediated untargeted metabolomic profiling of melanoma cells, to landscape metabolic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Metabolic reprogramming is a molecular hallmark of cancer that has also been substantiated in melanoma. However, even though GLO1 expression serves an essential function in the maintenance of glycolytic energy metabolism, the specific role of GLO1 in melanomagenesis remains largely unexplored [ 2 , 5 , 22 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic reprogramming is a molecular hallmark of cancer that has also been substantiated in melanoma. However, even though GLO1 expression serves an essential function in the maintenance of glycolytic energy metabolism, the specific role of GLO1 in melanomagenesis remains largely unexplored [ 2 , 5 , 22 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic re-programming is tightly associated with the tumor’s metastatic potential. Since the MCT1 lactate transporter (importer) plays diverse critical roles in the metastasis process [ 218 , 219 , 220 , 221 , 222 , 223 ], we next analyzed the cellular localization and distribution pattern of the MCT1 ( SLC16A1 /MOT1) transporter in WM115 and WM266-4 (2.70) ( Table S3 , [ 35 ]) melanoma cells ( Figure 7 C). Surprisingly, through immunofluorescence imaging, MCT1 was presented to strongly accumulate in the melanoma nucleus and not the cell membrane (as expected) for both cell types ( Figure 7 C).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that metabolism is significantly associated with tumorigenesis and metastasis ( Luengo et al, 2017 ; Kosmopoulou et al, 2020 ; Li et al, 2016 ). Based on the strategy of tumor immunotherapy with metabolic regulation, UHPLC-Q-TOF-MS technology was used.…”
Section: Resultsmentioning
confidence: 99%